NOD-like receptor repertoire in the chromosome-level genome of the demosponge Dysidea avara (Schmidt, 1862) - Koutsouveli, Vasiliki; Torres-Oliva, Montserrat; Marulanda-Gomez, Angela M.; Franke, Andre; Fuß, Janina; Schmitz, Ruth A.; Hentschel, Ute; Reusch, Thorsten B. H.; Pita, Lucía (Frontiers in Immunology, 2026)
Porifera, one of the earliest diverging metazoans, have shown a surprisingly complex immune repertoire. However, most information to date is based on de novo transcriptome assemblies, limiting our knowledge regarding the presence and evolution of poriferan immune repertoire. Here, we generated the chromosome-level genome of the demosponge Dysidea avara, a target species in studies on symbiosis and differential expression of immune genes. We examined the presence and the number of common immune protein domains in the annotated genome of D. avara, and we further focused on NOD-like Receptors (NLRs), which are one of the most expanded immune receptors in Porifera according to previous reports on draft genomes and transcriptome assemblies. Dysidea avara has a 575 Mb genome with N50 41Mb, 162 scaffolds, and 15 chromosomes. We additionally recovered 37 sequences corresponding to microbial genomes, including complete bacterial and viral genomes. Based on the presence of conserved domains, we detected a large number of immune receptors and other immune genes in D. avara genome, such as 14 TIR, 39 CARD, 128 DEATH, and 230 NACHT domain-containing genes. Based on their architecture, we identified a large expansion of bona fide NLRs (i.e., 126 NACHT+LRR domain-containing genes); of which, 20 included a N-terminal CARD domain (NLRC), and 25 included a N-terminal DEATH domain (NLRD). In D. avara, the different NLR categories (i.e., NLRX, NLRC and NLRD) formed distinct phylogenetic clusters, while the NLR phylogenetic analysis across sponge chromosome-level genomes indicated that NLRs were mainly grouped by species rather than category. The NLRX category was the most expanded, while the NLRC category was absent in 7 out of 11 studied sponge genomes. These observations indicate that the diversification of NLRs in sponges, most likely derived from the ancestor NLRX, responds to species-specific selective pressures related to their immunity. This is the first study characterizing sponge NLR diversity in a chromosome-level genome, enhancing our knowledge of NLR evolution in the ancient phylum Porifera.